INVESTIGASI KASUS COVID -19 OLEH PETUGAS KESEHATAN Di Puskesmas Tondano Selatan Kabupaten Minahasa: INVESTIGASI KASUS COVID -19 OLEH PETUGAS KESEHATAN Di Puskesmas Tondano Selatan Kabupaten Minahasa - lumowa, fresy (JURNAL ILMIAH KESEHATAN MANADO, 2022)
The first case of Covid-19 was found inIndonesia in March 2019, and has been declared by the government as a pandemic because of its rapid spread and transmission in the community and it is known that this virus attacks the human respiratory system which is infected by the presence of droplets entering through the respiratory system, so there is a need for strategies and actions to investigate Covid cases – 19 appropriate and fast ways to break the chain of transmission of this virus. The Puskesmas has formed an investigation officer for the Covid 19 case so that case handling can be immediately identified. The purpose of this study was to analyze the health workers at the Puskesmas in conducting investigations for the Covid 19 case. This study used a qualitative research design with an in-depth interview method with 5 respondents. The results of this study were found that the puskesmas conducted investigations of Covid-19 cases in the community by conducting investigations of Covid-19 cases in community members who were confirmed positive for Covid-19 and conducting investigations on community members with Close Contact (MCC) status and regular monitoring of patients with confirmed Covid-19 who carry out independent isolation at home for patients with Asymptomatic People (OTG) status and mild to moderate symptoms, as well as patients who have to be hospitalized because they have comorbidities. The Covid-19 investigation officers also encountered various obstacles in carrying out their duties, namely the attitudes and behavior of people who had not been able to comply with health protocols and people who were not cooperative by not wanting to go for a check-up. with the participation of the community in a commitment to implementing health protocols, namely wearing masks, washing hands, keeping a distance, reducing mobility and consuming healthy food (5M), where until now the 5M behavior of the community has not been optimally implemented so that the spread of Covid 19 cases is still high. Keywords: Investigation of covid 19 cases, Covid 19 Health Center Officers, Spread of Covid 19 VirusDownload Full File Disini